Effects of Cationic Dendrimers and Their Complexes with microRNAs on Immunocompetent Cells - Nadezhda Knauer; Ekaterina Pashkina; Alina Aktanova; Olga Boeva; Valeria Arkhipova; Margarita Barkovskaya; Mariya Meschaninova; Andrii Karpus; Jean-Pierre Majoral; Vladimir Kozlov; Evgeny Apartsin (MDPI AG, 2022)
Short regulatory oligonucleotides are considered prospective tools for immunotherapy. However, they require an adequate carrier to deliver potential therapeutics into immune cells. Herein, we explore the potential of polycationic dendrimers as carriers for microRNAs in peripheral blood mononuclear cells of healthy donors. As an oligonucleotide cargo, we use a synthetic mimic and an inhibitor of miR-155, an important factor in the development and functioning of immunocompetent cells. Dendrimers bind microRNAs into low-cytotoxic polyelectrolyte complexes that are efficiently uptaken by immunocompetent cells. We have shown these complexes to affect the number of T-regulatory cells, CD14+ and CD19+ cell subpopulations in non-activated mononuclear cells. The treatment affected the expression of HLA-DR on T-cells and PD-1 expression on T- and B-lymphocytes. It also affected the production of IL-4 and IL-10, but not the perforin and granzyme B production. Our findings suggest the potential of dendrimer-mediated microRNA-155 treatment for immunotherapy, though the activity of microRNA-dendrimer constructions on distinct immune cell subsets can be further improved.